PMN-MDSC and arginase are increased in myeloma and may contribute to resistance to therapy. (3rd July 2018) - Romano, Alessandra; Parrinello, Nunziatina Laura; La Cava, Piera; Tibullo, Daniele; Giallongo, Cesarina; Camiolo, Giuseppina; Puglisi, Fabrizio; Parisi, Marina; Pirosa, Maria Cristina; Martino, Enrica; Conticello, Concetta; Palumbo, Giuseppe Alberto; et al.
ABSTRACT: Objectives : Despite improvement in overall response due to the introduction of the first-in-class proteasome inhibitor bortezomib (btz), multiple myeloma (MM) is still an incurable disease due to the immune-suppressive bone marrow (BM) environment. Thus, the authors aimed to identify the role of CD11b + CD15 + CD14 − HLA-DR − granulocytic-like myeloid-derived suppressor cells (PMN-MDSC) in MM patients treated up-front with novel agents. Methods : In MM cell lines and primary cells derived by patients affected by MGUS and MM, we investigated sensitivity to bortezomib and lenalidomide in presence of Arg-1 and PMN-MDSC. Results : The authors found that PMN-MDSC and their function through increased arginase-1 (Arg-1) are associated with MM progression. When the authors assessed cell viability of the human myeloma cell lines MM1.s, OPM2 and U266 treated with 5–20 nM btz for 24 h in PMN-MDSC conditioned media, they disclosed that amount of Arg-1 and Arg-1 inhibition could affect btz sensitivity in-vitro . PMN-MDSC and Arg-1 were increased in peripheral blood of newly diagnosed MM patients compared to healthy subjects. PMN-MDSC and arginase were reduced after exposure to lenalidomide-based regimen but increased after btz-based treatment. Conclusion : In MM, Arg-1 is mainly expressed by PMN-MDSC. PMN-MDSC and Arg-1 are reduced in vivo after lenalidomide but not bortezomib treatment.